Elements that affect the effectiveness of occupational safety and health (OSH) in the construction project of the eye clinic in Batu City, as well as its impact on worker safety - Fifi Damayanti; Yurnalisdel Yurnalisdel; Dominikus Lubin (Asian Journal Science and Engineering, 2026)
This study aims to analyze the influence of aspects of occupational safety, occupational health, and work environment on work potential, work quality, and commitment and job satisfaction in the construction project of the ISHK Tolaram Eye Clinic in Batu City. The research uses a quantitative approach with questionnaire, observation, and interview instruments. Multiple linear regression, the t-test, and the F test were used to analyze the data using SPSS 27. The findings indicated that the aspect of occupational safety had a significant effect on work potential, while occupational health and work environment had no significant effect. Simultaneously, the three aspects of OSH have a significant effect on job potential, but not on quality or commitment and job satisfaction. These findings affirm the importance of occupational safety in increasing worker potential, while health and the work environment need to be strengthened to more optimally support productivity and labor satisfaction.